2019
DOI: 10.1038/s41419-019-1770-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA analysis in healthy individuals by next-generation sequencing: a proof of concept and technical validation study

Abstract: Pre-symptomatic screening of genetic alterations might help identify subpopulations of individuals that could enter into early access prevention programs. Since liquid biopsy is minimally invasive it can be used for longitudinal studies in healthy volunteers to monitor events of progression from normal tissue to pre-cancerous and cancerous condition. Yet, cell-free DNA (cfDNA) analysis in healthy individuals comes with substantial challenges such as the lack of large cohort studies addressing the impact of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 67 publications
7
61
1
Order By: Relevance
“…After preparation, libraries were quantified and showed a wide range of concentrations between 40.5-1440 pMol (median 450 pMol). As expected, it was observed that library yields increased proportionally with the amount of cfDNA ng employed per reaction (Spearman's correlation coefficient (r s ) = 0.67, p < 0.0001) ( Figure 2), a finding in line with literature [17].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…After preparation, libraries were quantified and showed a wide range of concentrations between 40.5-1440 pMol (median 450 pMol). As expected, it was observed that library yields increased proportionally with the amount of cfDNA ng employed per reaction (Spearman's correlation coefficient (r s ) = 0.67, p < 0.0001) ( Figure 2), a finding in line with literature [17].…”
Section: Resultssupporting
confidence: 89%
“…LoD evaluation through the samples revealed, not surprisingly, that higher quantities of cfDNA input allowed to reach very low levels of LoD (up to 0.02%), as also similarly reported by others [17], with the advantage to preserve specificity of the NGS workflow. It is interesting to note that at least 0.1% LoD was reached in 37/92 cases (40.22%).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In healthy individuals, cfDNA concentration ranges from 0 to 100 ng/mL of blood [33]. In comparison, cancer patients present on average four to 40 times greater levels, with an upper range exceeding 1000 ng/mL [34][35][36][37][38][39]. The higher cellular turnover observed in cancer would explain at least in part the higher plasmatic cfDNA levels observed.…”
Section: Genetic and Epigenetic Implications Of Cfdna In Cancer Diagnmentioning
confidence: 98%